2006
DOI: 10.1097/01.bpo.0000189970.37037.59
|View full text |Cite
|
Sign up to set email alerts
|

Hand Injuries in Children

Abstract: The purpose of this prospective clinical study was to identify the true incidence, pattern, and location of the injury and nature of fracture after hand injuries in different pediatric age groups attending a hand unit. Three hundred sixty children (237 boys, 123 girls) under 16 years of age who presented with hand injuries between April 1, 2000, and Sept. 30, 2000, were included in the study. Bony injuries accounted for 65.5% (236 injuries); 33.3% (120 injuries) were soft tissue injuries. The projected annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
76
4
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 8 publications
17
76
4
6
Order By: Relevance
“…The reported annual incidence rates showed wide ranges due to this studies have dealt with the pediatric population as a single group. 4,[11][12][13][14][15] Whereas there are very few studies on hand injuries in 0-6-year age group in the literature; in our country, studies in hand injuries of 0-16 years of age are also in limited number. Although, there are several studies analyzing epidemiology of hand injuries in children conducted in different countries and geographic regions, similar injury patterns seem to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported annual incidence rates showed wide ranges due to this studies have dealt with the pediatric population as a single group. 4,[11][12][13][14][15] Whereas there are very few studies on hand injuries in 0-6-year age group in the literature; in our country, studies in hand injuries of 0-16 years of age are also in limited number. Although, there are several studies analyzing epidemiology of hand injuries in children conducted in different countries and geographic regions, similar injury patterns seem to occur.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The rate of hand injuries among all patients admitted to a children's emergency department was reported to be 1-2.1% by Fetter-Zarzeka et al 3 Vadivelu et al reported the projected annual incidence rate for skeletal injuries for under 16 years of age group was 418/100,000. 4 Ljungberg et al reported the incidence of hospitalized children with hand and forearm injuries as 39.6/100,000 in the 0-6-year age group and 42.1/100,000 in the 7-14-year age group. 5 In our country, Bostancı et al stated that 8.6% of patients admitted to children's emergency clinics had upper extremity injuries.…”
mentioning
confidence: 99%
“…Of all phalangeal fractures, proximal phalanx fractures are most common [37,39]. They can be divided into base, shaft, neck, and condylar fractures.…”
Section: Proximal Phalanxmentioning
confidence: 99%
“…Metacarpal fractures can be divided into head, neck, shaft, and base fractures, with neck and shaft fractures being the most common [37,38]. Metacarpal head fractures in children are rare.…”
Section: Metacarpalmentioning
confidence: 99%
“…2 Injuries of the hand have been noted to have an enormous impact on hand function and on quality of life. 3 In this era of industrialization and reliance on machines, hand injuries are on the increase worldwide, accounting for 10-15 percent of admissions in emergency departments in the developed countries 4,5 . In Uganda's largest hospital 6% of all trauma admissions in the emergency department are hand injuries.…”
mentioning
confidence: 99%